2005
DOI: 10.1111/j.1537-2995.2005.00676.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐dependent up regulation of CD177‐specific mRNA expression in cord blood due to different stimuli

Abstract: These findings show a significantly increased CD 177 expression in neutrophils from newborns compared to adults, which suggests the existence of additional factors being able to stimulate CD 177 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…It is known that neutrophil CD177 expression can increase significantly in certain clinical conditions, such as severe bacterial infections and polycythemia vera [32]. Also a significant increased CD177 expression was found in neutrophils from newborns compared to adults, suggesting the existence of additional factors being able to stimulate CD177 expression [33]. Total CD177-deficiency in healthy donors is probably due to an abnormal insertion containing stop codon in the CD177gene [28], [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that neutrophil CD177 expression can increase significantly in certain clinical conditions, such as severe bacterial infections and polycythemia vera [32]. Also a significant increased CD177 expression was found in neutrophils from newborns compared to adults, suggesting the existence of additional factors being able to stimulate CD177 expression [33]. Total CD177-deficiency in healthy donors is probably due to an abnormal insertion containing stop codon in the CD177gene [28], [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that CD177 ϩ neutrophils express proteinase 3 as an additional, unique surface marker, probably defining them as a subpopulation with yet unknown functions in innate immunity (48). More importantly, a specific up-regulation of neutrophil CD177 has been demonstrated during bacterial infections, upon treatment with granulocyte-colony-stimulating factor, and during pregnancy as well as in newborns (9,49,50). This indicates that the CD177-dependent pathway could be utilized under certain (patho-)physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This proportion is a lifelong characteristic [10,59]. However, upon neutrophil activation in severe bacterial infections, in pregnancy and in newborns the expression can be upregulated [57,63,64,65,66]. …”
Section: Hna-2mentioning
confidence: 99%